IMPLEMENTASI KEBIJAKAN DISIPLIN PNS DALAM MENINGKATKAN EFEKTIVITAS PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - POMPAYO, JUNEIDI (JURNAL ADMINISTRASI PUBLIK, 2014)
The discipline policy implementation of  PNS how to as set in the PP. 53 years 2010 by the apparatus of subdistrict?s government be expected  can realize the effectiveness of the governance subdistrict. However, the fact remains that governance subdistrict not running optimally effective. In connection with this problem it is necessary to research on how the discipline policy implementation of  PNS in the employee Pasan subdistrict?s goverment, and what the discipline policy implementation of PNS has been increasing effectiveness of the governance subdistrict. Method used is qualitative method. Data sourch/informant taken from appratus elements/employee of subdistrict?s goverment as much as 9 peoples, and elements in the employee of Pasan subdistrict as much as 6, so that all informants as many as 15 people there. Data collection techniques using interview techniques. While the analysis of the data using qualitative analysis techniques interactive model of Miles and Hubernan. Research results show : (1) the discipline policy implementation of PNS in the apparatus/ employee Pasan subdistrict government is good enough but not maximum views from aspect tribute, appreciation, obedience, and docility employee on the basis of consciousness/conviction to regulation, standard norm or prevailing values; employee's ability to perform tasks and duties according to the rules, norms, standards or values ??that apply; and willingness and ability to accept and carry out the sanctions for breach of discipline. (2) effectiveness of governance subdistrict not optimal but is good enough views from level of ability and the success of implementing the program/implementation of general governance activities and implementation of regional autonomy matters in the scope of their duties or delegated by the Regents particularly meaningful public service. Based on that research result taken conclusion that PNS have the discipline policy implementation can improve the effectiveness of governance. Based on conclusion research result suggested the need for efforts to improve awareness in the apparatus Pasan subdistrict?s government about the importance of obeying and complying with all the provisions of the disciplinary rules PNS the taska and position. Keywords : the discipline policy implementation, effectiveness government of subdistrict